1997
DOI: 10.1063/1.475194
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic and correlated calculations on the ground, excited, and ionized states of iodine

Abstract: The electronic structure, spectroscopic, and bonding properties of the ground, excited, and ionized states of iodine are studied within a four-component relativistic framework using the MOLFDIR program package. The experimentally determined properties of the 1 ⌺ g ϩ ground state are well reproduced by our results calculated at the CCSD͑T͒ level of theory. Relativistic effects and corevalence correlation need to be included in order to get reliable results, but the Gaunt interaction can be neglected. The photoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
93
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(99 citation statements)
references
References 66 publications
4
93
2
Order By: Relevance
“…Since the goal of this paper is to demonstrate the application of the relativistic Fock space method in the context of molecular calculations, no extensive studies of basis set or active space convergence have been carried out. The contracted pVTZ basis set 20 and active space used are identical to the ones used in the earlier calculation of de Jong et al 21 on the same molecule, to facilitate comparison with the single reference CC approach. Thirty-four electrons were correlated, freezing 4p and deeper core orbitals, which give insignificant contributions when calculated in this basis.…”
Section: The I 2 Moleculementioning
confidence: 99%
See 1 more Smart Citation
“…Since the goal of this paper is to demonstrate the application of the relativistic Fock space method in the context of molecular calculations, no extensive studies of basis set or active space convergence have been carried out. The contracted pVTZ basis set 20 and active space used are identical to the ones used in the earlier calculation of de Jong et al 21 on the same molecule, to facilitate comparison with the single reference CC approach. Thirty-four electrons were correlated, freezing 4p and deeper core orbitals, which give insignificant contributions when calculated in this basis.…”
Section: The I 2 Moleculementioning
confidence: 99%
“…24 The spectroscopic constants for the 1 ⌺ g ϩ ground state of the neutral species ͑Table I͒ are in line with previous work. 21 The bond length is found to be about 5 pm too large, which is mainly due to truncation errors in the single particle basis. The calculated constants for the 2 ⌺ u ϩ ground state of the negative ion ͑Table II͒ are in reasonable agreement with the experimental values of Zanni et al 25 The error in the bond length ͑3-4 pm͒ is similar to that found for the neutral species, and is ascribed to the same source.…”
Section: The I 2 Moleculementioning
confidence: 99%
“…The energy changes due to difference in basis set are expected to be large as can be seen from the comparison of DC-FSCCSD and DC-FSCCSD+BSSE. DC-CCSD(T) values 29 imply that the contribution from triple excitations will be also important to estimate experiment result.…”
Section: Test Calculationsmentioning
confidence: 99%
“…heavy atoms and molecules, their applications to larger molecules are prohibitively demanding [4,5,7,8]. Hence, a great deal of attention is given to approximate methods which are based on the 2-spinor formalism [6,9,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%